All-solid-state lithium ion battery and application thereof

By using modified lithium-based composite negative electrodes and doped modified sulfide electrolytes in all solid state lithium-ion batteries, a stable interface layer is formed, which solves the stability and compatibility problems of sulfide electrolytes in applications and improves the energy density and cycling performance of the battery.

CN119695249AActive Publication Date: 2025-03-25ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411934055.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In actual applications, existing sulfide electrolytes have poor air stability and poor interface compatibility with lithium metal, which limits the development of all-solid-state lithium-ion batteries.

Method used

By using a modified lithium-based composite negative electrode and doped modified sulfide electrolyte in an all-solid-state lithium-ion battery, a stable negative electrode-solid electrolyte interface layer is formed to block the direct contact between the sulfide electrolyte and the lithium metal negative electrode, uniformize the current and lithium ion flux at the interface, and reduce the risk of lithium dendrites.

Benefits of technology

The stability of the conductivity of the sulfide electrolyte is improved, the stability of the air is enhanced, the interfacial properties of the electrolyte/active substance are improved, the compatibility with the active material is improved, and the energy density and circulation performance of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212826380000161
    Figure BDA0005212826380000161
Patent Text Reader

Abstract

The invention provides an all-solid-state lithium ion battery and application thereof. The all-solid-state lithium ion battery comprises a positive pole piece and a negative pole piece, according to the modified lithium-based composite negative electrode, a modified raw material comprises metal fluoride; the solid electrolyte membrane is arranged between the positive pole piece and the modified lithium-based composite negative pole, the solid electrolyte membrane comprises a sulfide electrolyte, and the chemical formula of the sulfide electrolyte is Li P < 1-b > M Sc < d > X < e >, a < lt >; 6, 0lt; blt; 1, 1.5 1t; clt; ct; 5, 0lt; dlt; 2.5, 4lt; c + dlt; 5, 1lt; lt, lt; 2; m is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from one or more of Cl, Br or I. According to the all-solid-state lithium ion battery and the application thereof provided by the invention, the conductivity and air stability of the sulfide electrolyte can be improved, a stable negative electrode-solid electrolyte interface layer can be formed, direct contact between the sulfide electrolyte and a lithium metal negative electrode is blocked, the risk of lithium dendrite generation is reduced, and the service life of the all-solid-state lithium ion battery is prolonged. The energy density and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly to an all-solid-state lithium-ion battery and its application. Background Art

[0002] With the continuous growth of the global demand for new energy vehicles, the requirements for the energy density, cycle life, safety, etc. of power batteries are becoming increasingly stringent. As a representative of the next-generation battery, solid-state batteries have become an important direction in the future energy storage field. Sulfide electrolytes for all-solid-state lithium-ion batteries have become a research hotspot in the energy storage field due to their ultra-high ionic conductivity and good processability. However, most sulfide electrolytes have problems such as poor air stability and poor compatibility with the lithium metal interface in practical applications, which limit the development of sulfide all-solid-state lithium-ion batteries. Summary of the Invention

[0003] The present invention provides an all-solid-state lithium-ion battery and its application. By using the all-solid-state lithium-ion battery and its application provided by the present invention, the conductivity stability of the sulfide electrolyte can be improved, the air stability can be enhanced, a stable negative electrode-solid electrolyte interface layer can be formed, which can block the direct contact between the sulfide electrolyte and the lithium metal negative electrode, homogenize the current and lithium ion flux on the interface, reduce the risk of lithium dendrite formation, and improve the energy density and cycle performance of the battery.

[0004] To solve the above technical problems, the present invention is realized through the following technical solutions.

[0005] The present invention provides an all-solid-state lithium-ion battery, comprising at least:

[0006] a positive electrode sheet;

[0007] a modified lithium-based composite negative electrode, the modification raw material including a metal fluoride; and

[0008] a solid electrolyte membrane disposed between the positive electrode sheet and the modified lithium-based composite negative electrode, the solid electrolyte membrane including a sulfide electrolyte, the chemical formula of the sulfide electrolyte being Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from one or more of Cl, Br or I.

[0009] In one embodiment of the present invention, M is selected from at least one of Sb, In or Bi, and X is selected from Cl.

[0010] In one embodiment of the present invention, the cation in the metal fluoride is selected from Ag + 、Al 3+ 、Zn 2+ Mg 2+ or Sn 2+ One or more of the following, wherein the anion in the metal fluoride is selected from F - PF6 - 、FSI - TFSI - 、BF4 - PF2O2 - 、ODFB - or ODFP - One or more of .

[0011] In one embodiment of the present invention, the cation is selected from Ag + , the anion is selected from PF2O2 - 、ODFB - or ODFP - At least one of .

[0012] In one embodiment of the present invention, the modified lithium-based composite negative electrode is obtained by the following method:

[0013] Weighing metallic lithium and metal fluoride in a stainless steel container according to the mass ratio, heating to a molten state, and cooling to room temperature after sufficient reaction to obtain a metal fluoride-modified lithium metal block; and

[0014] The metal fluoride-modified lithium metal block is placed on a roller press and repeatedly rolled to obtain the modified lithium-based composite negative electrode.

[0015] In one embodiment of the present invention, the mass ratio of the metal fluoride to the metal lithium is (10-60):100.

[0016] In one embodiment of the present invention, the heating and melting temperature is 200° C. to 300° C., and the reaction time is 0.5 h to 5 h.

[0017] In one embodiment of the present invention, the thickness of the modified lithium-based composite negative electrode is 10 μm to 100 μm, and the thickness of the solid electrolyte membrane is 30 μm to 100 μm.

[0018] In one embodiment of the present invention, the particle size of the sulfide electrolyte is 1 μm to 10 μm, and the ion conductivity is greater than 3 mS / cm.

[0019] In one embodiment of the present invention, the solid electrolyte membrane includes a sulfide electrolyte and a binder, and the content of the sulfide electrolyte in the solid electrolyte membrane is 80wt% to 99wt%; the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binder, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber.

[0020] The present invention also provides an electronic device, comprising the all-solid-state lithium-ion battery described above.

[0021] In summary, the present invention proposes an all-solid-state lithium-ion battery and its application, which can improve the stability of the conductivity of the sulfide electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material. The modified lithium-based composite negative electrode is formed with LiF and alloy phases, and the overall alloy phase has a high degree, which can accelerate the transmission of lithium ions, while reducing the side reactions of lithium metal and sulfide electrolyte at the interface, and improving the performance of the all-solid-state lithium-ion battery. The modified lithium-based composite negative electrode modified by metal fluoride and the doped modified sulfide electrolyte are matched and used in the all-solid-state lithium-ion battery to form a stable negative electrode-solid electrolyte interface layer, which can block the direct contact between the sulfide electrolyte and the lithium metal negative electrode, and can also make the current and lithium ion flux on the interface uniform, reducing the risk of lithium dendrite formation. At the same time, the energy density and cycle performance of the battery can be improved. DETAILED DESCRIPTION

[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0023] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0024] The technical solution of the present invention is further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The present invention provides an all-solid-state lithium-ion battery, which includes a positive electrode sheet, a modified lithium-based composite negative electrode, and a solid electrolyte membrane. In the present invention, the all-solid-state lithium-ion battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery, or a cylindrical battery. The present invention does not specifically limit the type and type of the all-solid-state lithium-ion battery.

[0026] In one embodiment of the present invention, the modified raw material for modifying the lithium-based composite negative electrode includes, for example, metal fluorides, wherein the cations in the metal fluorides are selected from, for example, Ag + 、Al 3+ 、Zn 2+ Mg 2+ or Sn 2+ One or more metal ions capable of alloying with lithium metal, such as F - PF6 - 、FSI - TFSI - 、BF4 - PF2O2 - 、ODFB - or ODFP - In one embodiment of the present invention, the cation is selected from Ag, + etc., and the anion is selected from PF2O2 - 、ODFB - or ODFP - At least one of the above can regulate the composition of the interface layer between the modified lithium-based composite negative electrode and the solid electrolyte membrane to improve the intrinsic ionic conductivity of the interface layer.

[0027] In one embodiment of the present invention, the modified lithium-based composite negative electrode is obtained by the following method:

[0028] Weighing metallic lithium and metal fluoride in a stainless steel container according to the mass ratio, heating to a molten state, and cooling to room temperature after sufficient reaction to obtain a metal fluoride-modified lithium metal block;

[0029] The metal fluoride-modified lithium metal block is placed on a roller press and repeatedly rolled to obtain the modified lithium-based composite negative electrode.

[0030] In one embodiment of the present invention, the heating melting temperature is 200°C to 300°C, the reaction time is 0.5h to 5h, for example 0.5h to 2h, and the heating is performed under an inert atmosphere, such as one or both of argon or helium, to ensure that the metal fluoride and the metal lithium react fully and avoid side reactions. The metal fluoride and the metal lithium react in a heated and molten state to form a lithium alloy phase with high ionic conductivity, which can quickly convert lithium ions (Li+ ) is transported from the bulk to the solid electrolyte interface to compensate for the loss of lithium.

[0031] In one embodiment of the present invention, the mass ratio of metal fluoride to metallic lithium is (10-60):100, and for example (20-40):100, and for example 20:100, 30:100, 40:100 or 50:100. Controlling the content of metal fluoride can form a stable interface layer between the modified lithium-based composite negative electrode and the solid electrolyte membrane, and the overall alloy phase of the modified lithium-based composite negative electrode is relatively high, which can accelerate the transmission of lithium ions. However, when the content of metal fluoride is high, there are too many LiF and alloy phases at the interface, and the excess LiF makes Li + The diffusion kinetics across the interface deteriorates, and the excess alloy phase accelerates the side reaction between the lithium metal and the sulfide electrolyte at the interface. When the content of metal fluoride is low, less lithium alloy phase is generated, and the improvement of lithium ion transmission is not obvious. Therefore, the mass ratio of metal fluoride to metallic lithium is controlled to improve the transmission performance of lithium ions, while reducing the side reaction between lithium metal and sulfide electrolyte at the interface, thereby improving the performance of all-solid-state lithium-ion batteries.

[0032] In one embodiment of the present invention, the rolling time of the metal fluoride-modified lithium metal block on the roller press is 1h to 3h. By controlling the speed and roller torque of the roller press, the thickness of the modified lithium-based composite negative electrode obtained is, for example, 10μm to 100μm, or 10μm to 80μm.

[0033] In one embodiment of the present invention, the solid electrolyte membrane is disposed between the positive electrode and the modified lithium-based composite negative electrode, and the solid electrolyte membrane includes a sulfide electrolyte, and the chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e, where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, Nb, etc., and X is selected from one or more of Cl, Br, I, etc. Introducing M element and O element into the P site and O site of the sulfide electrolyte rich in halogen elements will form P-O and M-S bonds in the crystal structure, thereby improving the inherent resistance to atmospheric degradation and effectively reducing the generation of H2S, enhancing the air stability and chemical stability of the sulfide electrolyte. In addition, when using this sulfide electrolyte to assemble a all-solid-state lithium-ion battery, alloys such as LiCl, Li2O, LiF, and Li-M can be formed in the electrolyte / negative electrode interface layer, which can ensure good electron insulation performance and at the same time ensure the rapid migration of ions at the interface, thereby improving the rate and cycle performance of the all-solid-state lithium-ion battery.

[0034] In an embodiment of the present invention, M is, for example, selected from at least one of Sb, In, or Bi. Since the ionic radii of Sb, In, or Bi are moderate, the ionic radii of these elements are close to those of the main elements in the sulfide electrolyte, such as sulfur and phosphorus. Therefore, when doping, they can more easily replace the positions of the main elements without causing excessive lattice distortion. And the electronegativity of Sb, In, or Bi is moderate, and they can form stable chemical bonds with the sulfur element in the sulfide, and are difficult to be damaged by external influences, so that the sulfide electrolyte has high stability and specific reactivity, can improve the stability of the conductivity of the sulfide electrolyte, enhance the air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material.

[0035] In an embodiment of the present invention, X is selected as a halogen element, and according to the different halogens, the degree of anion disorder between the 4a and 4c sites in the crystal structure of the sulfide electrolyte is different, from a small number of anti-site defects with X being I to 60% site disorder with X being Cl, and the lithium ionic conductivity of these compounds mainly depends on the degree of disorder of anion and cation site occupancy. Therefore, X is, for example, also selected as Cl to improve the ionic conductivity and electrochemical stability of the sulfide electrolyte and improve the voltage stability. The value range of b is 0 < b ≤ 0.1. In a specific embodiment of the present invention, when M is +5 valence, the best value of b is 0.04, and when M is +3 valence, the best value of b is 0.02 to improve the cycle performance of the lithium-ion battery.

[0036] In one embodiment of the present invention, the sulfide electrolyte is obtained by the following preparation method: according to the chemical formula of the sulfide electrolyte, a Li source, a P source, an M source, an S source and an X source are mixed in stoichiometric amounts, and then placed in a ball mill for ball milling to obtain a sulfide electrolyte precursor powder; the sulfide electrolyte precursor powder is calcined at a preset temperature to obtain a sulfide electrolyte.

[0037] In one embodiment of the present invention, according to the chemical formula of the sulfide electrolyte Li a P 1-b M b S c O d X e , the Li source, P source, M source, S source and X source are uniformly mixed according to stoichiometric ratio, wherein the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5, the M source is selected from one or more of oxides of M or sulfides of M, the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, As2S5, As2S3, Sb2S5, Sb2S3, Bi2S5, Bi2S3, Al2S3, Ga2S3, In2S3 or Sc2S3, the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, and the O element in the chemical formula comes from the oxide of M. After the raw materials are mixed evenly, they are placed in a ball mill and ball milled in an inert gas atmosphere, wherein the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1500 rpm, and the ball milling time is, for example, 1 h to 48 h, to obtain a sulfide electrolyte precursor powder.

[0038] In one embodiment of the present invention, the sulfide electrolyte precursor powder is calcined at a preset temperature, wherein the preset temperature is 400°C to 600°C, and the calcination time is 1h to 18h, to obtain a sulfide electrolyte. In one embodiment of the present invention, the particle size of the sulfide electrolyte is, for example, 1μm to 10μm, and the ion conductivity is greater than 3mS / cm.

[0039] In one embodiment of the present invention, after obtaining the sulfide electrolyte, a solid electrolyte membrane is obtained, for example, by dry preparation or wet preparation. In this embodiment, for example, a solid electrolyte membrane is obtained by dry preparation, specifically, the sulfide electrolyte and the binder are blended according to the mass ratio to obtain a mixed powder; the mixed powder is repeatedly rolled at a preset temperature for a preset time to obtain a solid electrolyte membrane. Among them, the content of the sulfide electrolyte in the solid electrolyte membrane is, for example, 80wt% to 99wt%, and the binder is, for example, selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber. The preset temperature is 60°C to 100°C, the preset rolling time is 30min to 120min, and the thickness of the obtained solid electrolyte membrane is, for example, 30μm to 100μm.

[0040] In one embodiment of the present invention, a modified lithium-based composite negative electrode modified by metal fluoride and a doped modified sulfide electrolyte are used in a fully solid-state lithium-ion battery. The anions in the metal fluoride generate LiF with low electronic conductivity at the interface between the two phases, and the doped modified solid electrolyte membrane forms LiCl with high interfacial energy and Li2O with high ionic conductivity at the interface. LiF, Li2O and LiCl together form a stable negative electrode-solid electrolyte interface layer. This stable interface layer can block the direct contact between the sulfide electrolyte and the lithium metal negative electrode, and can also make the current on the interface and Li + The flux is homogenized to reduce the risk of lithium dendrite formation.

[0041] In one embodiment of the present invention, the positive electrode sheet includes, for example, a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric, and the thickness of the positive electrode current collector is, for example, 8 μm to 15 μm.

[0042] In one embodiment of the present invention, the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a conductive agent, and a binder, wherein the positive electrode active material is selected from, for example, a positive electrode active material with a layered structure, such as one or more combinations of lithium cobalt oxide (LCO), nickel cobalt manganese lithium oxide (NCM), or nickel cobalt aluminum lithium oxide (NCA). The positive electrode active material is selected from, for example, an olivine structured positive electrode active material, such as one or more combinations of lithium iron phosphate (LFP) or lithium iron manganese phosphate (LFMP). The positive electrode active material is selected from, for example, a spinel structured positive electrode active material, such as one or more combinations of lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), or lithium-rich manganese-based (LMR).

[0043] In one embodiment of the present invention, the positive electrode active material is, for example, LiNbO3 coated LiNi 0.9 Co 0.05 Mn 0.05 O2, wherein the coating layer has a thickness of, for example, 5 nm to 15 nm. In this embodiment, the positive electrode active material is obtained, for example, by a wet coating method. By coating with LiNbO3, the discharge capacity and cycle stability of the all-solid-state lithium-ion battery can be improved, the mechanical properties of the material can be enhanced, and the service life of the battery can be extended.

[0044] In one embodiment of the present invention, the positive electrode electrolyte is, for example, the above-mentioned sulfide electrolyte. The conductive agent is, for example, selected from one or more combinations of conductive carbon black (Super P), nanocarbon fiber (Vapor-grown Carbon Fiber, VGCF), Ketjen black, acetylene black, graphene, carbon nanotubes, porous carbon, etc., and the binder is, for example, selected from one or more combinations of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene butadiene rubber (SBR), etc.

[0045] In one embodiment of the present invention, the positive electrode active material is, for example, LiNbO3 coated LiNi 0.9 Co 0.05 Mn 0.05O2, the positive electrode electrolyte is, for example, the above-mentioned sulfide electrolyte, the conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1, and the binder is, for example, HNBR. The positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are dispersed in a low-polarity solvent such as xylene according to a mass ratio of 70:25:2:3, and the amount of xylene added is adjusted to control the solid content of the slurry to, for example, about 55%. The slurry is coated on an aluminum foil by a doctor blade method, and the coated aluminum foil is air-dried at 90°C to 110°C for 2h to 3h, and then rolled and compacted at 60°C at a pressure of 95MPa to obtain a positive electrode sheet, and the thickness of the positive active layer is, for example, 80μm to 120μm. The present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder, and can be selected according to actual needs.

[0046] In one embodiment of the present invention, the above-mentioned positive electrode sheet, solid electrolyte membrane and modified lithium-based composite negative electrode are placed in sequence, so that the solid electrolyte membrane is between the positive electrode sheet and the modified lithium-based composite negative electrode to play an isolating role, and the sheets are stacked to form a bare cell. The bare cell is placed in a shell and sealed, and the shell is, for example, an aluminum-plastic bag, and then placed, formed and divided into different volumes to obtain a finished soft-pack all-solid-state lithium-ion battery. Among them, the assembly process of the all-solid-state lithium-ion battery is completed in a glove box with an inert atmosphere.

[0047] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0048] Example 1

[0049] Preparation of modified lithium-based composite negative electrode: In an argon atmosphere glove box, silver hexafluorophosphate and metallic lithium were mixed in a stainless steel tank in a mass ratio of 20:100, heated at 300°C for 1 hour to obtain a molten melt, and then the melt was cooled to room temperature to obtain a metal fluoride-modified lithium metal block. The metal fluoride-modified lithium metal block was repeatedly rolled at room temperature to a thickness of 30 μm to obtain a modified lithium-based composite negative electrode.

[0050] Preparation of solid electrolyte membrane: Li 5.54 P 0.98 In 0.02 S 4.4 O 0.1 Cl 1.5 and PTFE binder at a mass ratio of 99:1 for 5 minutes, then roll-pressed at 80°C, gradually narrowing the roll gap to 40 μm, and repeatedly rolling at this roll gap for 60 minutes to obtain a solid electrolyte membrane with a thickness of 40 μm.

[0051] Preparation of positive electrode sheet: LiNi coated with LiNbO3 positive electrode active material 0.9 Co 0.05 Mn 0.05 O2, the coating thickness is 10nm. The positive electrode electrolyte is, for example, the above-mentioned sulfide electrolyte, the conductive agent includes Super P and VGCF, and the mass ratio of Super P and VGCF is 1:1, and the binder is HNBR. In an environment with a dew point of -30°C, the positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are dispersed in xylene, for example, according to a mass ratio of 70:25:2:3, and the amount of xylene added is adjusted to control the solid content of the slurry to 55%. The slurry is coated on an aluminum foil by a doctor blade method, and the coated aluminum foil is dried at 100°C for 2h, and then rolled and compacted at 60°C at a pressure of 95MPa to obtain a positive electrode sheet, wherein the thickness of the positive electrode active layer is, for example, 100μm.

[0052] All-solid-state lithium-ion battery assembly: stack the prepared positive electrode sheet, solid electrolyte membrane and modified lithium-based composite negative electrode in sequence, so that the solid electrolyte membrane is between the positive electrode sheet and the modified lithium-based composite negative electrode to play an isolating role, and stack the sheets to the bare battery cell. Put the bare battery cell into an aluminum-plastic bag, and then stand it, form it and divide it into different volumes to obtain a finished soft-pack all-solid-state lithium-ion battery.

[0053] Example 2

[0054] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 1.

[0055] Example 3

[0056] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 P 0.96 Sb 0.04 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0057] Example 4

[0058] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Al 0.02 S 4.4 O 0.1 Cl 1.5, other operations remain the same as those in Example 1.

[0059] Example 5

[0060] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Ti 0.02 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0061] Example 6

[0062] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.99 Bi 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 1.

[0063] Example 7

[0064] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.62 P 0.94 Bi 0.06 S 4.1 O 0.09 Cl 1.5 , other operations remain the same as those in Example 1.

[0065] Example 8

[0066] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 1.

[0067] Example 9

[0068] When preparing the modified lithium-based composite negative electrode, the mass ratio of silver hexafluorophosphate to metallic lithium was 10:100, and other operations were consistent with Example 1.

[0069] Example 10

[0070] When preparing the modified lithium-based composite negative electrode, the mass ratio of silver hexafluorophosphate to metallic lithium is 60:100, and other operations are consistent with Example 1.

[0071] Embodiment 11

[0072] When preparing the modified lithium-based composite negative electrode, the mass ratio of silver hexafluorophosphate to metallic lithium is 100:100, and other operations are consistent with Example 1.

[0073] Example 12

[0074] When preparing the modified lithium-based composite negative electrode, silver hexafluorophosphate was replaced by silver fluoride, and other operations were consistent with Example 1.

[0075] Example 13

[0076] When preparing the modified lithium-based composite negative electrode, silver hexafluorophosphate was replaced by silver bis(fluorosulfonyl)imide, and other operations were consistent with Example 1.

[0077] Embodiment 14

[0078] When preparing the modified lithium-based composite negative electrode, silver hexafluorophosphate was replaced by silver tetrafluoroborate, and other operations were consistent with Example 1.

[0079] Embodiment 15

[0080] When preparing the modified lithium-based composite negative electrode, silver hexafluorophosphate was replaced by silver difluorooxalate borate, and other operations were consistent with Example 1.

[0081] Example 16

[0082] When preparing the modified lithium-based composite negative electrode, silver hexafluorophosphate was replaced by zinc difluoride, and other operations were consistent with Example 1.

[0083] Embodiment 17

[0084] When preparing the modified lithium-based composite negative electrode, silver hexafluorophosphate was replaced by tin difluoride, and other operations were consistent with Example 1.

[0085] Embodiment 18

[0086] When preparing the modified lithium-based composite negative electrode, silver hexafluorophosphate was replaced by magnesium difluoride, and other operations were consistent with Example 1.

[0087] Comparative Example 1

[0088] When preparing the modified lithium-based composite negative electrode, the mass ratio of silver hexafluorophosphate to metallic lithium is 0:100, that is, the negative electrode is lithium metal, and other operations are consistent with Example 1.

[0089] Comparative Example 2

[0090] When preparing the modified lithium-based composite negative electrode, the mass ratio of silver hexafluorophosphate to metallic lithium is 0:100, that is, the negative electrode is lithium metal, and other operations are consistent with Example 8.

[0091] Comparative Example 3

[0092] When preparing the modified lithium-based composite negative electrode, silver hexafluorophosphate was replaced by ferric fluoride, and other operations were consistent with Example 1.

[0093] Comparative Example 4

[0094] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 In 0.02 S5Cl 1.5 , other operations remain the same as those in Example 1.

[0095] Comparative Example 5

[0096] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 PS 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0097] Comparative Example 6

[0098] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is replaced by Li-ion coated with 15 nm thick ZrO2. 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 1.

[0099] In Examples 1-18 and Comparative Examples 1-6 of the present invention, different sulfide electrolytes and modified lithium-based composite negative electrodes are used to prepare all-solid-state lithium-ion batteries, and some characteristics of the sulfide electrolytes and modified lithium-based composite negative electrodes are shown in Table 1. The all-solid-state lithium-ion batteries obtained in Examples 1-18 and Comparative Examples 1-6 are tested, and the test results are shown in Table 1.

[0100] In one embodiment of the present invention, the modified lithium-based composite negative electrode obtained in Examples 1-18 and Comparative Examples 1-6 is used to assemble a symmetrical battery in the order of a modified lithium-based composite negative electrode, a solid electrolyte membrane, and a modified lithium-based composite negative electrode. The solid electrolyte membrane is located between the two modified lithium-based composite negative electrodes to play an isolating role. The symmetrical battery limiting current density (CCD) is measured. Specifically, 0.1 mA / cm 2 The lithium deposition and stripping tests were carried out for 1 h at a current density of 0.1 mA / cm 2 The increase gradually increases. When the symmetrical battery short-circuits, the test is stopped and the current density at this time is recorded.

[0101] In one embodiment of the present invention, the 0.5C / 0.5C room temperature cycle capacity retention rate test of the all-solid-state ion battery is to charge and discharge the prepared all-solid-state lithium ion battery at a low rate of 0.1C / 0.1C for 2 weeks at 25°C, and the test voltage range is 2.5-4.2V, and then charge and discharge at a rate of 0.5C / 0.5C, and record the first cycle discharge capacity at a rate of 0.5C. When the discharge capacity reaches 80% (80% SOH) of the first cycle discharge capacity at a rate of 0.5C, the test stops and the number of cycles at room temperature is recorded. The calculation formula for the capacity retention rate is as follows: Capacity retention rate (%) = (discharge capacity / discharge capacity of the first cycle) × 100%.

[0102] Table 1. Battery performance test results in Examples 1-18 and Comparative Examples 1-6

[0103]

[0104] As shown in Table 1, by comparing Examples 1-18 and Comparative Examples 1-6, it can be seen that the combined use of a doped modified sulfide electrolyte and a metal fluoride modified lithium-based composite negative electrode can effectively alleviate the interfacial side reactions between the sulfide electrolyte and lithium metal, regulate the migration and deposition / stripping behavior of lithium ions at the negative electrode, and inhibit the formation of lithium dendrites at high current rates, thereby improving the first efficiency and cycle performance of all-solid-state lithium-ion batteries.

[0105] Please refer to Table 1. By comparing Examples 1 and 8 with Comparative Examples 1 and 6, it can be seen that, compared with modifying the sulfide electrolyte alone or modifying the lithium metal negative electrode alone, the present invention can greatly improve the cycle and rate performance of the all-solid-state lithium-ion battery. When the sulfide electrolyte is coated and modified and used in combination with a modified lithium-based composite negative electrode modified by a metal fluoride, the battery performance is weaker than the doped modified sulfide electrolyte provided in this application. This is because when the doped modified sulfide electrolyte and the modified lithium-based composite negative electrode modified by a metal fluoride are used in combination, the metal fluoride reacts with metallic lithium to generate a lithium alloy phase with higher ionic conductivity and LiF with lower electronic conductivity. The lithium alloy can quickly convert Li + LiF is transported from the bulk to the solid electrolyte interface to compensate for the loss of lithium, while LiF can make the current on the interface and Li + The flux is homogenized. At the same time, the modified sulfide electrolyte forms a high interfacial energy LiCl and a high ionic conductivity Li2O at the interface. LiF, Li2O and LiCl together form a stable negative electrode-solid electrolyte interface layer. This stable interface layer can block the direct contact between the sulfide electrolyte and the lithium metal negative electrode, and can also make the current on the interface and Li + The flux is uniformed to prevent lithium dendrites from piercing the electrolyte membrane and causing a short circuit in the battery.

[0106] Please refer to Table 1. Comparative Examples 1-7 show that when different elements and contents are doped in the sulfide electrolyte, the influence on the limiting current density of the symmetrical battery is greater. Among them, the limiting current density of the symmetrical battery doped with indium, bismuth and antimony elements is better than that of aluminum and titanium elements, and the corresponding all-solid-state lithium-ion battery has better cycle performance. Comparative Example 1 and Comparative Examples 4-5 show that when the P and O positions are single-doped, the limiting current density of the symmetrical battery is low and the battery cycle performance is poor. Therefore, when the P and O positions are double-doped, the limiting current density of the symmetrical battery is better than that of the single-point element doping, and the cycle life of the corresponding battery is also longer.

[0107] Please refer to Table 1. By comparing Examples 1, 9 to 11, it can be seen that as the ratio of metal fluoride to lithium increases, the limiting current density and cycle number of the symmetrical battery first increase and then decrease. This is because when the metal fluoride content is high, there are too many LiF and alloy phases at the interface, and the excess LiF makes Li + The diffusion kinetics across the interface deteriorates, and the excess alloy phase accelerates the side reaction between the lithium metal and the sulfide electrolyte at the interface. When the metal fluoride content is low, the bulk phase is dominated by lithium metal, and LiF exists in some areas of the interface layer, which makes it difficult to prevent the formation of lithium dendrites.

[0108] Please refer to Table 1. It can be seen from Comparative Examples 1, 12-15 that for fluorides of different anions, when the anions contain atoms other than fluorine atoms, substances such as Li3P, Li3B or Li3N may appear in the interface layer to jointly regulate the transmission of interface ions, and the cycle life of the corresponding battery is slightly improved. Comparative Examples 12, 16-18 and Comparative Example 3 show that fluorides of different cations have different improvements on the limiting current density of symmetrical batteries and the number of cycles of all-solid-state lithium-ion batteries. This is because the lithium ion conductivity of alloys formed by the combination of different cations and lithium metals is different, resulting in differences in the performance of all-solid-state lithium-ion batteries.

[0109] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state lithium-ion batteries, and the all-solid-state lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state lithium-ion battery, and therefore includes the advantages of the above-mentioned all-solid-state lithium-ion battery, which will not be elaborated here.

[0110] In summary, the present invention proposes an all-solid-state lithium-ion battery and its application, which can improve the stability of the conductivity of the sulfide electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material. The modified lithium-based composite negative electrode is formed with LiF and alloy phases, and the overall alloy phase has a high degree, which can accelerate the transmission of lithium ions, while reducing the side reactions of lithium metal and sulfide electrolyte at the interface, and improving the performance of the all-solid-state lithium-ion battery. The modified lithium-based composite negative electrode modified by metal fluoride and the doped modified sulfide electrolyte are matched and used in the all-solid-state lithium-ion battery to form a stable negative electrode-solid electrolyte interface layer, which can block the direct contact between the sulfide electrolyte and the lithium metal negative electrode, and can also make the current and lithium ion flux on the interface uniform, reducing the risk of lithium dendrite formation. At the same time, the energy density and cycle performance of the battery can be improved.

[0111] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0112] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. An all-solid-state lithium-ion battery, characterized in that: include: Positive electrode; A modified lithium-based composite negative electrode, wherein the modified raw material includes metal fluoride; as well as A solid electrolyte membrane is disposed between the positive electrode sheet and the modified lithium-based composite negative electrode. The solid electrolyte membrane includes a sulfide electrolyte, and the chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, and X is selected from one or more of Cl, Br, or I.

2. The all-solid-state lithium-ion battery according to claim 1, characterized in that: M is selected from at least one of Sb, In and Bi, and X is selected from Cl.

3. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The cation in the metal fluoride is selected from Ag + 、Al 3+ 、Zn 2+ Mg 2+ or Sn 2+ One or more of the following, wherein the anion in the metal fluoride is selected from F - PF6 - 、FSI - TFSI - 、BF4 - PF2O2 - 、ODFB - or ODFP - One or more of .

4. The all-solid-state lithium-ion battery according to claim 3, characterized in that: The cation is selected from Ag + , the anion is selected from PF2O2 - 、ODFB - or ODFP - At least one of .

5. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The modified lithium-based composite negative electrode is obtained by the following method: Weighing metallic lithium and metal fluoride in a stainless steel container according to the mass ratio, heating to a molten state, and cooling to room temperature after sufficient reaction to obtain a metal fluoride-modified lithium metal block; and The metal fluoride-modified lithium metal block is placed on a roller press and repeatedly rolled to obtain the modified lithium-based composite negative electrode.

6. The all-solid-state lithium-ion battery according to claim 5, characterized in that: The mass ratio of the metal fluoride to the metal lithium is (10-60):

100.

7. The all-solid-state lithium-ion battery according to claim 5, characterized in that: The heating melting temperature is 200° C. to 300° C., and the reaction time is 0.5 h to 5 h.

8. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The thickness of the modified lithium-based composite negative electrode is 10 μm to 100 μm, and the thickness of the solid electrolyte membrane is 30 μm to 100 μm.

9. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The particle size of the sulfide electrolyte is 1 μm to 10 μm, and the ion conductivity is greater than 3 mS / cm.

10. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The solid electrolyte membrane comprises a sulfide electrolyte and a binder, wherein the content of the sulfide electrolyte in the solid electrolyte membrane is 80wt% to 99wt%; the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binder, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber.

11. An electronic device, characterized in that: A fully solid-state lithium-ion battery comprising any one of claims 1 to 10.

Citation Information

Patent Citations

  • Composition, energy storage device, and related processes

    CN103928661A

  • Solid-state composite metal lithium negative electrode

    CN108511708A

  • Sulfide all-solid-state battery and preparation method thereof

    CN117154012A

  • Preparation method and application of lithium argyrodite type solid electrolyte and sulfide film

    CN117457972A

  • Preparation method and application of lithium metal solid electrolyte membrane

    CN118054016A